IN REGARDS TO CONSTANT AND INTERPRETATIVE CRITERIA OF CONCEPT IN A LANGUAGE - M. N. Fedulova (MGIMO University Press, 2014)
The article is devoted to the research about the criteria for defining the "concept" in the modern linguistics. The existence of a number of concepts and terms doesn't allow the scientists to agree on its clear definition. The author points out that the base of concept emergence is founded on the processes of conceptualization, these processes are supported by the basic types of metaphorical judgment. In this article, the analysis of different approaches in order to define the structure of the concept indicates that the concept structure consists of a number of components, and for the most part they are permanent and the rest are interpretative. Until recently the linguistic development of "concept" was mainly limited by the framework of subject-thematic criteria. Along with this the scientists focused on and are still focusing on non-contradictory construction of concept logic in a language discourse. The author of the article states that the forming of the notions and perceptions about space, time, life is based on the conceptualization processes and reflected in the language and concepts. The understanding of concept is being achieved through the number of notions revealed during the speaking process, i.e. discursively, as well as through images, symbols, expression of feelings, and different emotional states. The evaluation of different occurrences, emerged within a certain situation is considered the beginning of the concept emergence. Thus, the author is inclining, that the concept is transsituational; its status is cognitive because the thinking process plays an important role in the cognition of the concept. It is particularly interesting to note the author's conclusion that it is incorrect to mix this important philosophical and linguistic notion with the notion/definition of "word". 'Word' is an objective side of conceptualization and it can not be considered a 'concept'. With all that the processes of conceptualization in the language can be considered in two ways: semasiologically and onomosemasiologically.